(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the process of designing a product, reverse engineering is essential, especially when original documentation is absent. It centres on copying key characteristics from a current object to produce more accurate or improved virtual or physical representations. This frequently calls for the reproduction of a Computer-Aided Design (CAD) model using a variety of digitization processes, allowing for more analysis and product design advancements. The process includes a number of tasks, such as segmenting structures, characterization of geometric models, and creation of precise CAD models. Reverse engineering has numerous applications in industries including manufacturing, product design, and archaeology and has a significant impact on the transition from physical products to digital designs. The research paper dives into the fundamental ideas and methods guiding this procedure, with a focus on how 3D data is obtained using tools like coordinate measuring machines (CMMs) and laser scanning.